Natural Medicinal Flora of Three Gorges of Yangtze River (Part of Rare and Endangered Medicinal Plants) - Shaocheng Chen; Xin Zhao; Jianhong Ke (Natural Medicinal Flora of Three Gorges of Yangtze River (Part of Rare and Endangered Medicinal Plants), 2021)
The Three Gorges of the Yangtze River starts from Baidi City, Fengjie County, Chongqing City in the West and ends at nanjinguan, Yichang City, Hubei Province in the East, with a total length of 193 km. Along the way, the two sides of the Yangtze River have steep peaks and steep cliffs, which are rich in plant resources. This book aims to provide information on natural medicinal plants in the Three Gorges region of China for researchers and practitioners of traditional Chinese medicine. In this book, the natural environment, vegetation composition, distribution law and floristic composition of natural medicinal plants in the Three Gorges area are comprehensively combed, and color maps are provided. This book has a good guiding role for professionals, and can be used as a corresponding reference book.